Beyond autonomy: unpacking self-regulated and self-directed learning through the lens of learner agency- a scoping review - Nidhi Gupta; Kamran Ali; Dan Jiang; Trine Fink; Xiangyun Du (BMC Medical Education)
Abstract Background Learner agency involves students actively engaging in their learning process and shaping their educational experiences through autonomy, self-regulation, and decision-making. In professional education, particularly within health professions, learner agency is critical for fostering adaptability and lifelong learning. This scoping review explores how learner agency, alongside concepts such as self-regulated learning and self-directed learning, is addressed in undergraduate dental education, aiming to understand its implications and strategies for enhancing student agency in this context. Methods The scoping review examined literature on self-regulated learning, self-directed learning and learner agency in undergraduate dental education from 1994-April 2024 across five databases: PubMed, Scopus, Embase, ProQuest Central, and Web of Science. A manual search of the cited references was also conducted. Relevant studies were screened, and the findings were summarized to offer a comprehensive overview and identify research gaps. Results In total, 33 studies were included in the review. The results revealed a strong interconnection between intrapersonal, behavioral, and contextual dimensions in shaping learner agency through self-regulated learning and self-directed learning among undergraduate dental students. The studies analyzed, predominantly quantitative, highlighted the multifaceted relationships among self-regulated learning and self-directed learning and learner agency, emphasizing its significance for educational practice and policy. Conclusions Self-regulated learning and self-directed learning are crucial for developing learner agency, aiding undergraduate students’ transition into independent professionals and fostering lifelong learning behaviors. Educational strategies should prioritize empowering students to become independent learners, reducing their reliance on faculty. Further research is needed to identify effective methods for promoting learner agency development among dental students.